Exploring Parental Support of Online Learning at Kota Palangka Raya Elementary School - Prasetiawati, Prasetiawati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
All countries in the world are now making various efforts to prevent the spread of Covid-19 so that there are no additional positive patients that increase every day, and the latest effort is the provision of vaccines which have now been implemented in several countries including Indonesia. However, it cannot be denied that even though the vaccine has been carried out, the spread of the Covid-19 virus still continues and threatens the safety of human life. The spread of Covid-19 since 2020 until now and has made several negative impacts in all lines of life that is felt by all Indonesian people, especially the economic, social and educational sectors. In online learning, the role of parents is also very necessary. The role of parents in online learning is to have a role as a teacher at home, as a facilitator, as a motivator and as a director. Wiradimadja believes that currently many parents are not ready to become teachers for their children. They are not able to provide good education and mentoring for their children